Radiofrequency ablation of anteroseptal accessory pathway – A challenge to the electrophysiologist - Vukmirović, Mihailo Čedomir; Angelkov, Lazar; Vukmirović, Filip; Vukmirović, Irena Tomašević (Vojnosanitetski pregled, 2015)
Introduction. Anteroseptal accessory pathways (APs) are located in the apex of the triangle of Koch’s connecting the atrial and ventricular septum in the region of the His bundle. Ablation of anteroseptal pathway locations remains a challenge to the electrophysiologist due to a very high risk of transiet or permanent atrioventricular (AV) block. Case report. A male, 18-year-old, patient was hospitalized due to radiofrequency (RF) ablation of APs. He was an active football player with frequent palpitations during efforts accompanied by dyspnea and lightheadedness, but without syncope. Electrocardiography on admission showed intermittent preexcitations. Intracardiac mapping showed the earliest ventricular activation that preceded surface electrocardiographic delta wave in anteroseptal region very close to the AV node and His bundle. Using a long vascular sheath for stabilization of the catheter tip, RF energy was delivered at the target site starting at very low energy levels and because of the absence of either PR prolongation, as well as accelerated junctional rhythm during the first 15 sec, the power was gradually increased to 40W, so after application RF energy preexcitation was not registered. Conclusion. Despite this proximity to the His bundle and very high risk of transiet or permanent AV block anteroseptal APs can still be ablated successfully.
Keywords: heart conduction system; arrhythmias; cardiac; catheter ablation; treatment outcome